In pursuit of a high temperature, high pressure, high viscosity standard: the case of TOTM! - Wakeham, William A. (2017)
Excel file for the viscosity and density calculation for Tris(2-ethylhexyl) trimellitate (TOTM), CAS 3319-31-1, a liquid being proposed as a high viscosity at high pressure and high temperature industry standard fluid.